Telemedicine for emergency patients in pre-hospital care: A scoping review (Jurnal Ilmu Kesehatan Masyarakat, 2022)
Pre-hospital care is the initial phase of emergency management for patients with acute conditions. Emergency patients' mortality rates can be lowered with appropriate pre-hospital care. The utilization of telemedicine has been increasing rapidly, and one of its applications is the provision of pre-hospital care. This study aimed to identify and evaluate published research on the use of telemedicine to facilitate emergency patient management in pre-hospital care. ProQuest, Scopus, EMBASE, and EBSCOhost databases were used for article search and PRISMA flow diagram was used to perform the articles selection. The search results obtained 443 articles. Title and abstract screening removed 347 articles, leaving 41 to be assessed for eligibility. Articles relevant to the study question and meet the criteria were 14 articles. Most of the studies were conducted in developed countries. The use of telemedicine has a significant potential to improve the quality of pre-hospital care provided to emergency patients, by aiding in diagnosis and treatment selection for patient’s better outcomes. However, to establish this system, a well-organized EMS system is required. Nevertheless, the use of this technology requires more development, and additional study is required in the future.